Densidad poblacional de Saguinus oedipus (Primates Callitrichidae) y disponibilidad de alimento vegetal, Colosó, Sucre - Colombia (2014)
The present study analyzes for Saguinus oedipus, endemic species of the Colombian Caribbean, the existing relationship between populational density and vegetable food availability in a tropical dry forest fragment at the Colosó stream, in the department of Sucre, Colombian. In the forest fragment the results of presence absence show that are available 55.8% families and 44.9% species in concordance with the reports as vegetables that are food for S. oedipus. Specifically, were registered as vegetable food 17 families and 26 species, what represents a use of 58.6% families and 18.8% species from the total established. For the two detected groups, according to historical registrations, the populational density is comparatively low and the proportions between sexes, males: females (1:2 y 1:1.6) varies notably with the established for the species. Be concluded that the habitat quality related to food offer determines the populational size and influences the proportions between sexes.